2021
DOI: 10.1002/edn3.260
|View full text |Cite
|
Sign up to set email alerts
|

The development of early monitoring tools to detect aquatic invasive species: eDNA assay development and the case of the armored catfish Hypostomus robinii

Abstract: Introductions of invasive non‐native species (and their subsequent impacts) are recognized as a major threat to native flora and fauna. This is especially true in island ecosystems such as the tropical island of Martinique. In 2018, one such aquatic invasive species, the suckermouth catfish Hypostomus robinii (Loricariidae), was reported for the first time in two of the islands rivers. H. robinii is a popular freshwater aquarium fish and native to tropical and sub‐tropical South America. Since its initial disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Environmental DNA methods have also been used successfully for the detection and monitoring of invasive fish (Takahara et al 2013; Keskin 2014; Bylemans et al 2016; Keskin et al 2016; Hinlo et al 2017; Clusa and García-Vázquez 2018; Jo et al 2021; Minett et al 2021; Dubreuil et al 2022; Jeunen et al 2022). Considerable efforts have been made to barcode introduced freshwater fish species in South Africa (van der Walt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental DNA methods have also been used successfully for the detection and monitoring of invasive fish (Takahara et al 2013; Keskin 2014; Bylemans et al 2016; Keskin et al 2016; Hinlo et al 2017; Clusa and García-Vázquez 2018; Jo et al 2021; Minett et al 2021; Dubreuil et al 2022; Jeunen et al 2022). Considerable efforts have been made to barcode introduced freshwater fish species in South Africa (van der Walt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This further highlights the importance of using multi-marker approaches, which include the use of genes such as Cytb that have more complete reference libraries, for eDNA studies in South Africa. Environmental DNA methods have also been used successfully for the detection and monitoring of invasive fish (Takahara et al 2013;Keskin 2014;Bylemans et al 2016;Keskin et al 2016;Hinlo et al 2017;Clusa and García-Vázquez 2018;Jo et al 2021;Minett et al 2021;Dubreuil et al 2022;Jeunen et al 2022). Considerable efforts have been made to barcode introduced freshwater fish species in South Africa (van der Walt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Two respiratory organs corroborate this, the fish's gills and labyrinth. The gills' primary organs are inhaled in clear water, whereas the labyrinth is used by organisms living in mud or dirty water [32]. The findings of studies [35] conducted around the Cirata Reservoir's floating net cages revealed similar effects, notably low DO at the bottom owing to the breakdown of organic matter, mainly feed leftovers, which use oxygen in the waters.…”
Section: Rainy Season Dry Seasonmentioning
confidence: 97%
“…According to field studies, the suckermouth catfish (Hypostomus plecostomus), an invasive fish from South America and a demersal fish [32], regularly rises to the surface to acquire oxygen. This indicates that oxygen at the bottom of the water is insufficient to meet the fish's respiration demands.…”
Section: Rainy Season Dry Seasonmentioning
confidence: 99%
“…In freshwater ecosystems, the first species‐specific eDNA‐based approach was developed by Ficetola et al (2008), proving its effectiveness to detect an invasive frog ( Rana catesbeiana ) in France. Since a large number of studies and methodological development were conducted to improve eDNA‐based applications (Schenekar, 2022), in particular as an aquatic conservation tool to monitor taxa of interest (e.g., invasive, rare, threatened taxa), using eDNA collected from river water samples (e.g., Atkinson et al, 2019; Dubreuil et al, 2021; Harper et al, 2018; Piggott, 2016). However, detection and interpretation of eDNA signals from water samples in rivers can be challenging due to natural dilution, degradation (environmental factors, biological processes), and transport conditions (Barnes & Turner, 2015).…”
Section: Introductionmentioning
confidence: 99%